2015
DOI: 10.1002/ajmg.a.37028
|View full text |Cite
|
Sign up to set email alerts
|

Community dissemination and genetic research: Moving beyond results reporting

Abstract: The community-based participatory research (CBPR) literature notes that researchers should share study results with communities. In the case of human genetic research, results may be scientifically interesting but lack clinical relevance. The goals of this study were to learn what kinds of information community members want to receive about genetic research and how such information should be conveyed. We conducted 8 focus group discussions with Yup’ik Alaska Native people in southwest Alaska (N=60) and 6 (N=61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Representative examples include studies of 20 participants in a United Kingdom trial of prenatal antibiotics 19 ; 24 potential participants (or parents of potential participants) in a study testing children for neurodevelopmental deficits 22 ; 44 participants in a United Kingdom dementia study 23 ; 135 U.S. participants in a phase II trial of breast excision as breast cancer treatment 24 ; 409 Canadian and U.S. parents of children with cancer and 86 adolescents with cancer 20 ; 540 Ugandan participants in observational research on living with HIV 25 ; and 121 potential participants in genetic research, including 60 Seattle members of a health maintenance organization and 61 Yup'ik Alaska Native people. 21 These studies document sample-specific concerns and preferences; broadly, their results converge most conclusively upon the basic finding that study participants would like to receive research results.…”
mentioning
confidence: 64%
“…Representative examples include studies of 20 participants in a United Kingdom trial of prenatal antibiotics 19 ; 24 potential participants (or parents of potential participants) in a study testing children for neurodevelopmental deficits 22 ; 44 participants in a United Kingdom dementia study 23 ; 135 U.S. participants in a phase II trial of breast excision as breast cancer treatment 24 ; 409 Canadian and U.S. parents of children with cancer and 86 adolescents with cancer 20 ; 540 Ugandan participants in observational research on living with HIV 25 ; and 121 potential participants in genetic research, including 60 Seattle members of a health maintenance organization and 61 Yup'ik Alaska Native people. 21 These studies document sample-specific concerns and preferences; broadly, their results converge most conclusively upon the basic finding that study participants would like to receive research results.…”
mentioning
confidence: 64%
“…Most previous studies of participants' experiences, preferences, and perceptions with respect to the dissemination of research findings show that participants have a high desire to receive findings; however, these studies focused on specific diseases (Dixon-Woods et al 2006; Partridge et al 2005; Fernandez et al 2009; Baylor et al 2013; Trinidad et al 2015). Therefore, it has been difficult to determine participants' general beliefs and preferences for the dissemination of research findings.…”
mentioning
confidence: 99%
“…In addition, individual results may be offered results if other conditions are met (National Heart Lung Blood Institute working group et al 2010). Since then, studies have identified support for disclosing personal genomic results from genomic study participants (Allen et al 2014;Bollinger et al 2012;Halverson and Ross 2012;Overby et al 2015;Trinidad et al 2015), researchers (Appelbaum et al 2015;Meacham et al 2010), IRB committee members (Beskow and O'Rourke 2015;Dressler et al 2012), ethicists and lawyers (Burke et al 2014;Evans 2014;Thorogood et al 2014;Wolf et al 2015), and two genomics research networks ). In addition, NHLBI (2010) recommended that Binvestigators conducting research with identifiable communities should engage the community on the return of aggregate and/or individual research results^, and other researchers concurred (Lemke et al 2012;Marsh et al 2013;Overby et al 2015;Trinidad et al 2015).…”
Section: Discussionmentioning
confidence: 99%